Inkoherensi Fatwa Majelis Ulama Indonesia tentang Dukungan terhadap Perjuangan Palestina dan Sertifikasi Produk Halal - Rosita, Muamalah; Purbasari, Indah (Al-Qisthu, 2024)
Fatwa Number 83 of 2023 by the Indonesian Council of Ulama (MUI) prohibits transactions with products affiliated with Israel, while Law No. 33 of 2014 on Halal Product Assurance, which grants MUI the authority to issue halal certification, does not include such a prohibition. This study examines the applicability of MUI Fatwa No. 83 of 2023 regarding the certification of products affiliated with Israel, using a juridical-empirical research method with a qualitative approach. The research concludes that there is no clear legal consequence for the halal certification of products affiliated with Israel following the issuance of the fatwa. The MUI has not provided clarity regarding the prohibition of using halal products affiliated with Israel, resulting in legal uncertainty and ambiguity about the halal status of these products and whether they will be accepted for halal certification. There are no derivative regulations regarding the halal certification status of products affiliated with Israel, leading to differing interpretations among halal support institutions. One institution includes products affiliated with Israel on a list of products deemed unfit for certification, while another considers them eligible for certification.